Analysis of preoperative and postoperative depression and anxiety in patients with lumbar disc herniation with radiculopathy treated with percutaneous transforaminal endoscopic discectomy - Wei, Yatao; Huang, Hailun; Sun, Kui; Gao, Heng; Cao, Zhenwen; Zhang, Bin; Wu, Junzhe; Liu, Yongai (Frontiers in Psychiatry, 2024)
This study aims to examine the mental health of patients with lumbar disc herniation with radiculopathy (LDHR) and to evaluate the effects of percutaneous transforaminal endoscopic discectomy (PTED) on their mental well-being. Method: This study included 114 LDHR patients who received PTED in the Spinal Orthopedics Department of Zhongshan Hospital of Traditional Chinese Medicine between May 2022 and May 2023. The study population was stratified into two groups according to the presence of preoperative anxiety and depression: Group A comprised patients with such symptoms, and Group B included the remainder. Patients were assessed using the Hospital Anxiety and Depression Scale (HADS), the Visual Analog Scale for Pain (VAS), and the Oswestry Disability Index (ODI) at preoperative and final follow-up visits. Evaluations were performed using the Hospital Anxiety and Depression Scale (HADS), the Visual Analog Scale, and the Oswestry Disability Index (ODI) at the time of preoperation and during the last follow-up. Results: Among the 114 LDHR patients who obtained complete follow-up, fifty-four had anxiety/depression symptoms before surgery, which accounted for a incidence of 47%. Both Group A and Group B patients showed significant improvement in all evaluation indicators after PTED, but the overall prognosis of Group A was worse than that of Group B. Conclusion: PTED can effectively improve patients' pain, functional activities and mental health, which has a positive impact on patients' quality of life, and there is a significant correlation between patients' preoperative mental health and prognosis.